Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/molecules25081768
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Anti-Inflammatory and Anti-Oxidative Stress Activities of Kushenol C Isolated from the Roots of Sophora flavescens

Abstract: Kushenol C (KC) is a prenylated flavonoid isolated from the roots of Sophora flavescens aiton. Little is known about its anti-inflammatory and anti-oxidative stress activities. Here, we investigated the anti-inflammatory and anti-oxidative stress effects of KC in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages, and tert-butyl hydroperoxide (tBHP)-induced oxidative stress in HaCaT cells. The results demonstrated that KC dose-dependently suppressed the production of inflammatory mediators, including NO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…LPS serving as an important component is present in the cell wall of Gram-negative bacteria, which can be widely used to stimulate macrophages to induce inflammation through binding to receptors on the membrane of macrophages [36]. LPS promotes macrophages to release numerous proinflammatory mediators and cytokines [37]. In addition, oxidative stress is also an important factor of boosting inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…LPS serving as an important component is present in the cell wall of Gram-negative bacteria, which can be widely used to stimulate macrophages to induce inflammation through binding to receptors on the membrane of macrophages [36]. LPS promotes macrophages to release numerous proinflammatory mediators and cytokines [37]. In addition, oxidative stress is also an important factor of boosting inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Sophora flavescens is also used in the traditional Chinese medicine for the treatment of gastrointestinal hemorrhage, skin diseases and pyretic stranguria, and has been confirmed in many studies to have antitumor, antiviral and anti-inflammatory properties [ 1 , 2 , 3 , 4 ]. Phytochemical studies have also confirmed the presence of quinolizidine alkaloids and prenylated flavonoids, which, interestingly, have demonstrated pharmacological activities as antitumor, antiviral and anti-inflammatory agents, thus confirming the pharmacological benefits of Kushen as depicted in traditional Chinese medicine [ 5 , 6 , 7 ]. One of the prenylated flavonoids isolated from Kushen is Kushenol C (KC).…”
Section: Introductionmentioning
confidence: 86%
“…One study reported that KC possesses greater antioxidant activities, by preventing the generation of reactive oxygen species in a liver cell line, compared to other prenylated flavonoids such as kushenol A, 8-prenylkaempferol, formononetin and 8-prenylnaringenin isolated from the roots of S. flavescens [ 8 ]. We previously reported that KC inhibited the activation of signal transducer and activator of transcription 1 (STAT1), STAT6, and nuclear factor kappa B (NF-κB) in a stimulated macrophage cell line and upregulated the activation of nuclear factor erythroid 2-related factor 2 (Nrf2) and Akt in the phosphoinositide 3-kinase (PI3K)-Akt signaling pathway in a skin cell line, thereby conferring anti-inflammatory and antioxidative stress properties to KC [ 7 ]. KC was shown to inhibit the activities of cytochrome P450, the drug-metabolizing enzyme and drug transporter that plays a central role in the metabolism and elimination of drugs in the liver [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry analysis was performed as previously described ( 22 ). The primary antibodies used were as follows: Anti-NLRC3 (1:500), anti-TRAF6 (1:500) and anti-NF-κB p65 (1:500), and an HRP-conjugated anti-rabbit antibody was used as the secondary antibody (Abcam; cat.…”
Section: Methodsmentioning
confidence: 99%